2017
DOI: 10.1002/jin2.25
|View full text |Cite
|
Sign up to set email alerts
|

The curious case of how mimicking physiological complexity in in vitro models of the human respiratory system influences the inflammatory responses. A preliminary study focused on gold nanoparticles

Abstract: Environmental and biomedical nanoparticles can pose potential health risks to the human respiratory system by inducing severe lung inflammation. The aim of this case study is to present a comparison of the inflammatory response in four in vitro models of the human lung epithelium, differing by composition and/or culturing substrates, when exposed to gold nanoparticles (AuNPs). Three in vitro models of lung adenocarcinoma (A549) cells and a commercially available three-dimensional (3D) culture (MucilAir ™ ) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 123 publications
(143 reference statements)
2
11
0
Order By: Relevance
“…This result suggests that there was a polarized secretion of cytokines by the epithelial cells into the apical compartment. This has been previously reported by other research groups for various human lung cell lines (including A549 cells) grown on Transwell™ membranes [ 26 , 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This result suggests that there was a polarized secretion of cytokines by the epithelial cells into the apical compartment. This has been previously reported by other research groups for various human lung cell lines (including A549 cells) grown on Transwell™ membranes [ 26 , 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 81%
“…Cultures of human lung (A549) cells grown at the air–liquid interface (ALI) were tested as in vitro test model. A549 cells are an accepted model for the risk assessment of inhaled NP because they mimic the alveolar epithelium, which is the primary region where most inhaled NPs deposit [ 26 ]. Currently, in vitro models of the human lung epithelium used for NP risk assessment can vary in their complexity level [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the scientific literature 42 46 , our results confirmed that the 3D spatial architecture of the cultures influenced the F-actin organization within the cells. While A549 cells in 2D are well-known to be characterized by F-actin stress-fibers 47 , in ALI multilayered mono-cultures the adenocarcinoma cell line showed a cortical organization of the F-actin (Fig. 2A , and Supporting video VS1).…”
Section: Resultsmentioning
confidence: 91%